2006
DOI: 10.3354/dao072031
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and herpesvirus infections of the Pacific oyster Crassostrea gigas in Tomales Bay, California, USA

Abstract: Seed losses of Pacific oysters Crassostrea gigas have been associated with an ostreid herpesvirus-1 (OsHV-1) in Europe, and in 2002, a similar OsHV was detected in Tomales Bay, California, USA. In May of 2003, 5 stocks of seed Pacific oysters were planted at 2 sites (Inner Bay and Outer Bay) in Tomales Bay and monitored for mortality, presence/prevalence of OsHV (using polymerase chain reaction [PCR] and histology), and growth. Temperature (°C) and salinity data were collected every half an hour at each site.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
108
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 28 publications
16
108
0
Order By: Relevance
“…parasite identity in conjunction with differential staining used to elucidate subcellular components linked to a specific taxon. Although viral morphology cannot be observed using light microscopy, microscopic observations of cellular changes may suggest a specific aetiology such as a specific viral infection [80,81] or suggest viral type [75]. Pathogen presence can then be confirmed using additional special stains or molecular methods (described below) and morphology can be confirmed using electron microscopy [82].…”
Section: (D) Tissues and Cellsmentioning
confidence: 99%
“…parasite identity in conjunction with differential staining used to elucidate subcellular components linked to a specific taxon. Although viral morphology cannot be observed using light microscopy, microscopic observations of cellular changes may suggest a specific aetiology such as a specific viral infection [80,81] or suggest viral type [75]. Pathogen presence can then be confirmed using additional special stains or molecular methods (described below) and morphology can be confirmed using electron microscopy [82].…”
Section: (D) Tissues and Cellsmentioning
confidence: 99%
“…Furthermore, microarray-based gene expression studies have observed elevated expression of genes associated with autophagy in Crassostrea gigas undergoing a mass mortality event in California, USA (Moreau et al, 2015). Chaney & Gracey (2011) did not investigate the cause of mortality, but OsHV-1 is often associated with oyster mortality in California (Burge et al, 2006). Future research should identify which OsHV-1 ligand induces autophagy and whether autophagy targets the OsHV-1 virion or an essential OsHV-1 protein.…”
Section: Programmed Cell Death (Pcd)mentioning
confidence: 99%
“…The first description of herpes-like virus associated with mollusc mortality was reported in 1972 in the Eastern oyster (Crassostrea virginica) from the east coast of the USA (Farley et al, 1972). Since this time, herpes-like viruses have been described in other species of oyster (Burge et al, 2006;Hine et al, 1992;Renault et al, 1994), scallops (Arzul et al, 2001a;Ren et al, 2013) and clams (Renault et al, 2001). The virus has been purified from naturally infected Crassostrea gigas larvae (Le Deuff & Renault, 1999) and its genome entirely sequenced (Davison et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the observation by electron microscopy of capsids or nucleocapsids in the nucleus and virus particles in the cytoplasm or in cytoplasmic vesicles could only confirm the presence of a herpesviruslike and/or a viral disease [10,[18][19][20][22][23][24].…”
Section: Diagnosismentioning
confidence: 99%
“…Regarding the histopathological examination, what can be observed are the typical signs of a viral infection: connective tissue cells with pycnosis, nuclear changes (moon shaped), including nuclei hypertrophy with marginated chromatin, and large intranuclear acidophilic inclusion bodies (Cowdry type A inclusions) [10,[18][19][20][21]. Moreover, the observation by electron microscopy of capsids or nucleocapsids in the nucleus and virus particles in the cytoplasm or in cytoplasmic vesicles could only confirm the presence of a herpesviruslike and/or a viral disease [10,[18][19][20][22][23][24].…”
Section: Diagnosismentioning
confidence: 99%